EVALUASI PERAWATAN PADA COLD STORAGE SANKOOL DI PERUSAHAAN DAERAH RUMAH POTONG HEWAN SURABAYA - Dea Nabilah Idraki; Zainal Arief (Jurnal Taguchi : Jurnal Ilmiah Teknik dan Manajemen Industri, 2023)
PD. Rumah Potong Hewan Surabaya is a regionally owned company that operates in abattoir services. This company has a Commercial Unit that has existed for the past 10 years. . This variety of raw meat reaches 150 types of meat and beef innards which are never lacking in demand. Demand is always increasing, making the company maintain Cold Storage temperature conditions so as not to cause damage to the meat. The company will plan a routine maintenance schedule and will invest in a Sankool Cold Storage machine with a price of IDR 200,000,000 and an economic life of 10 years. The results of the analysis obtained by planning scheduling using the Preventive Maintenance method, namely the optimal interval for maintenance of cooling fan components is once every 9 days. The value of the reliability level that was successfully achieved was 61.67%. The results of data processing also show a decrease in costs before the proposal of IDR 17,000,000, and after the proposal of IDR 11,943,732 per year, or a decrease in costs of IDR 5,056,268 or 29%.